2020
DOI: 10.1136/thoraxjnl-2019-213732
|View full text |Cite
|
Sign up to set email alerts
|

Chronic obstructive pulmonary disease and lung cancer incidence in never smokers: a cohort study

Abstract: There has been limited evidence for the association between chronic obstructive pulmonary disease (COPD) and the incidence of lung cancer among never smokers. We aimed to estimate the risk of lung cancer incidence in never smokers with COPD, and to compare it with the risk associated with smoking. This cohort study involved 338 548 subjects, 40 to 84 years of age with no history of lung cancer at baseline, enrolled in the National Health Insurance Service National Sample Cohort. During 2 355 005 person-years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 12 publications
1
73
2
Order By: Relevance
“…A link between microbial infections and the development of cancer has been demonstrated. COPD is an important independent risk factor for lung cancer ( 47 , 48 ). Chronic inflammation is a key characteristic of COPD ( 49 ).…”
Section: Microorganisms Inflammation and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…A link between microbial infections and the development of cancer has been demonstrated. COPD is an important independent risk factor for lung cancer ( 47 , 48 ). Chronic inflammation is a key characteristic of COPD ( 49 ).…”
Section: Microorganisms Inflammation and Cancermentioning
confidence: 99%
“…The isolation and characterization of individual circulating tumor cells (CTCs)-associated white blood cells (WBCs) (CTCs–WBCs) as well as corresponding cancer cells within each CTCs–WBCs cluster showed that neutrophils and CTCs interact within the blood, and this interaction promotes cell cycle progression, which enhances the possibility of tumor metastasis of CTCs ( 61 ). COPD is at high risk of lung cancer ( 48 ). Non-typeable Haemophilus influenzae (NTHi) colonization can increase the frequency of exacerbations of COPD ( 62 ).…”
Section: Microorganisms Inflammation and Cancermentioning
confidence: 99%
“…COPD and the ICS user have clear operational de nitions (6,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Operational De Nitionsmentioning
confidence: 99%
“…The potential causes include genetics, notably the EGFR mutation [ 4 ] in Asian females. Other factors are residential radon [ 5 ], chronic obstructive pulmonary disease [ 6 ] and being underweight [ 7 ]. The effects of alcohol consumption are disputed: it seemed to have a positive effect on the disease in Spanish women [ 8 ], but a larger meta-analysis suggested that abstinence (as opposed to moderate consumption of wine or spirits) was not beneficial [ 9 ].…”
Section: Introductionmentioning
confidence: 99%